Target recognition of indoor trolley for humanoid robot based on piecewise fitting method. (11th April 2019) - Zhang, Lei; Liu, Huiling; Luo, Chengfang; Bian, Gui‐Bin; Wu, Wanqing
Summary: Although several studies have considered the problem of humanoid robots pushing carts, only a few have focused on the problem of robots moving heavy objects under monocular vision. This study proposes a target recognition and positioning method and a control method for a robot pushing a loaded trolley. A control system based on the humanoid robot NAO is developed and a monocular visual ranging method with segmented fitting is proposed to realize hardware control and target search and positioning for NAO. The ability of NAO to push a small cart with various weights using visual positioning is tested. The experimental results show that the average error of the monocular distance measurement method is 1.7 mm and that the target search and positioning is accurate. NAO can push a loaded cart that is 6.5 times its own weight.